Indigenous Māori knowledge and perspectives of ecosystems - Harmsworth, Garth R; Awatere, Shaun (Ecosystem services in New Zealand : conditions and trends, 2013)
A framework/model based on Māori knowledge, values and perspectives is presented that distinguishes ‘cultural values’ from ‘cultural services’ and extends the deﬁnition of cultural values across the whole ecosystem services framework. Māori aspirations and well-being are interdependent on ecosystems and ecosystem services. Ultimately Māori wish to use these ecosystem approaches and frameworks to increase participation and inclusion in decision-making, to achieve multidimensional aspirational goals and desired indigenous outcomes.
Keywords: decision making; environment; environmental management; planning; policy making

Navigating towards marine co-management with Indigenous communities on-board the Waka-Taurua - Maxwell, Kimberley H.; Ratana, Kelly; Davies, Kathryn K.; Taiapa, Caine; Awatere, Shaun (Marine Policy, 2020)
Developing equitable marine management systems that recognise Indigenous worldviews, values, and practices, alongside international initiatives such as Ecosystem-Based Management (EBM) are paramount in countries which aim to recognise Indigenous rights. This is the case for New Zealand (NZ) where Indigenous-Māori rights to partner with the Government for the purpose of environmental management were guaranteed under the Treaty of Waitangi, 1840, and subsequent Acts (e.g. Resource Management Act, 1991). Our aim was to explore how both Indigenous-Māori and NZ societal values can be integrated into a marine co-management decision-making framework. Here we describe the Waka-Taurua (double-canoe) framework, and how it can be applied in developing a NZ marine management system (NZ-MMS), which includes both kaitiakitanga (a Māori concept of reciprocal care between Indigenous-Māori people and their territorial environment), and EBM, equitably. We argue that the Waka-Taurua framework can improve how marine co-management systems are developed by facilitating a more structured and equitable discussion of both Indigenous-Māori and broader societal worldviews, values, and practices.
Keywords: environmental management; governance; kaitiakitanga; kāwanatanga; water management